PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP MINAT BELI PRODUK SMARTPHONE XIOMI PADA DUTA CELL BIMA - NURLIATI NURLIATI; Irma Mardian (Universitas Sarjanawiyata Tamansiswa, 2021)
Naskah Diterima : Revisi Naskah :Diterima Untuk Terbit:Tersedia Online: The purpose of this study was to determine and analyze the effect of product quality, brand image and price perception on buying interest in Xiomi smartphone products at Duta Cell Bima. This type of research is associative, using primary data sources with quantitative data types. The research instrument used was a questionnaire with a Likert scale. The data collection techniques used were observation, interview, questionnaire and literature study. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation, determination test, t test and f test. Based on the results of the statistical t test, it shows that product quality, brand image and price perception partially do not have an effect on the purchase intention of Xiomi Smartphone products at Duta Cell Bima. Simultaneously, product quality, brand image and price perception affect the purchase interest of Xiomi Smartphone products at Duta Cell Bima. Keywords :Product Quality, Brand Image, Price Perception, Purchase Intention